Nursing experience of intradermal needle therapy in improving sleep quality of a patient with insomnia (皮内针改善1例失眠患者睡眠质量的护理体会) - ZHANG Nan (张楠); BAI Yu (白羽); MA Huigai (马会改) (Association of Integrative Nursing, 2021)
This paper summarized the nursing experience of one case of insomnia treated by intradermal needle therapy. Based on the acupoint selection by syndrome differentiation, the intradermal needle therapy combined with auricular acupuncture was carried out to relief patient's anxiety states and improve sleep quality. (本文总结 1 例皮内针改善失眠患者睡眠质量的护理经验, 包括中医辨证、皮内针操作方法以及注意事项等。通过采用皮内针体针与耳针相结合辨证取穴的方法治疗失眠, 能有有效缓解患者焦虑情绪, 改善睡眠质量。)